Relationship between morphometric and mechanical properties of superficial lumbosacral soft tissue layers in healthy young adults - Grześkowiak, Marcin; Kocur, Piotr; Łochyński, Dawid (Frontiers in Physiology, 2023)
Introduction: The myotonometry is a noninvasive method capable to quantify linear elastic and viscoelastic properties of the myofascial tissue. However, this superficial layer contains different structures that have different distribution and organization of structural components. Methods: Myotonometric measurements of dynamic stiffness, logarithmic decrement and creep and ultrasonographic measurements of cutaneous tissue, subcutaneous tissue, thoracolumbar fascia and lumbar multifidus muscle thickness and echogenicity were obtained from 50 healthy individuals in the resting prone position and during contralateral arm lift. Results: The most important findings were that, both in the relaxed and contracted lumbar multifidus state, the dynamic stiffness strongly negatively (r=-0.69; p<0.001 in relaxation, r=-0.83; p<0.001 in contraction) and creep strongly positively (r=0.79; p<0.001 in relaxation, r=0.85; p<0.001 in contraction) correlated with thicknesses of subcutaneous tissue. With lumbar multifidus contraction, the relative increase in dynamic stiffness was negatively correlated with relative decrease in dermis (r=-0.51; p<0.001) and subcutaneous tissue (r=-0.47; p=0.001), as well as positively correlated with relative increase in lumbar multifidus (r=0.36; p=0.010) thickness. Discussion: In conclusion, the amount of dynamic stiffness and creep of superficial soft tissues in the lumbar region predominantly depends on subcutaneous thickness either during the LM relaxation or isometric contraction. Elasticity is barely affected by soft tissues thickness. Mechanical parameters does not depend on the echogenicity. However it must be underscored that echogenicity reflects but does not measure the density of particular layers of superficial soft tissues. Therefore, when performing the myotonometric measurements and analysis of soft tissue parameters, one should take into consideration potential differences in the subcutaneous tissue thickness before any conclusive statements about the changes in mechanical parameters of myofascial tissue will be made.